2008
DOI: 10.1007/s00417-008-0973-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cosmetically tinted soft contact lenses on higher-order wavefront aberrations and visual performance

Abstract: Cosmetically tinted contact lenses increase ocular higher-order aberrations and worsen contrast sensitivity under both photopic and mesopic conditions. Increases in higher-order aberrations are responsible for decreased contrast sensitivity under the photopic condition. Tinted contact lens wearers should be sufficiently informed about the possible reduction in optical quality of the eye and quality of vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…Asymmetrical changes in optics may induce increases in comalike aberrations. 105 Poorly fitting tinted contact lenses showed significantly larger HOAs compared with well-fitting tinted lenses, although wavefront measurements were performed in a static fashion and not in a dynamic fashion. 106 A recent study reported that decorative, tinted contact lenses significantly increased ocular HOAs and decreased the contrast sensitivity with a decrease in the diameter of the pigment-free optical zone.…”
Section: Contact Lens Movement and Fittingmentioning
confidence: 99%
“…Asymmetrical changes in optics may induce increases in comalike aberrations. 105 Poorly fitting tinted contact lenses showed significantly larger HOAs compared with well-fitting tinted lenses, although wavefront measurements were performed in a static fashion and not in a dynamic fashion. 106 A recent study reported that decorative, tinted contact lenses significantly increased ocular HOAs and decreased the contrast sensitivity with a decrease in the diameter of the pigment-free optical zone.…”
Section: Contact Lens Movement and Fittingmentioning
confidence: 99%
“…There were also no differences in subjective appreciation or clinical performance between lens designs or lens powers. Other studies found various effects on HOA with differing spherical soft contact lens brands [21][22][23][24][25][26][27][28][29], which presumably drove the development of aspheric or 'aberration-free' lenses, along with the reports of the possible benefits of aspheric lenses [30][31][32][33]. This study found no changes in spherical aberration, but it did find changes in other aberrations.…”
Section: Discussionmentioning
confidence: 79%
“…Our data agree with those of Hiraoka et al, 10 who Optical quality parameters (mean T SD) before and after wearing the iris-coloring soft contact lenses also found this increase, even in spherical-like aberrations. 10 Other publications also found an increase in ocular aberrations, but with the use of clear soft contact lenses. 10,20Y23 This increase could be caused by influences of contact lens properties themselves (different hydration of the lens in its clear vs. tinted area, structural deformations at the junction between the two zones), 10,11,24 decentering of the lens with blinking (0.5 to 1 mm on a blink), 10 and tear film instability as a consequence of the use of contact lenses.…”
Section: Discussionmentioning
confidence: 96%
“…10 Other publications also found an increase in ocular aberrations, but with the use of clear soft contact lenses. 10,20Y23 This increase could be caused by influences of contact lens properties themselves (different hydration of the lens in its clear vs. tinted area, structural deformations at the junction between the two zones), 10,11,24 decentering of the lens with blinking (0.5 to 1 mm on a blink), 10 and tear film instability as a consequence of the use of contact lenses. 10,24Y26 To explain our results, we have applied the schematic model of Díaz 27 to reproduce the retinal optical quality of a middleaged emmetropic subject from our population, 28 and we furthermore evaluated paraxially the shift in the position of the pupil of entry with the contact lens according to the calculation method developed by Díaz.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation